KEBIJAKAN LUAR NEGERI INDONESIA DIBIDANG POLITIK DAN EKONOMI DALAM UPAYA UNTUK MEMBANGUN STABILITAS NASIONAL PADA MASA AWAL ORDE BARU (1967-1971) (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study is to describe foreign policy in the field of politics and economics in the early days of the New Order. The method used is the historical research method, namely the study of other sources containing information about the past and carried out systematically. Based on the results of research showing in the political field, Indonesia in the New Order era took a policy to normalize relations between Indonesia and Malaysia, this was based on the condition of the Indonesian economy which was hit by prolonged inflation since the Old Order era. Re-entered as a member of the United Nations and formed the ASEAN regional organization (Association of South East Asia Nations). In the economic field, the steps taken are rescheduling foreign debt, good relations with western countries, this can be proven by the formation of the IGGI (Intergovernment Group On Indonesia). integrating the Indonesian economic system with the economic system of liberalism as the fruit of the New Order Technocrats' thoughts, the correlation is that foreign investment is allowed to enter through the Foreign Investment Law. The results of this study can be concluded, the direction of foreign policy in the early New Order era was to improve the Indonesian economy, establish good relations with the west with the IGGI, strengthen relations with the Southeast Asian region with the existence of ASEAN and stop confrontation.Keywords: New Order Foreign Policy, New Order National Stability